2020
DOI: 10.5430/ijhe.v9n1p237
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Stress in In-service Chinese University Teachers of Arts

Abstract: As revealed by literature, anxiety and stress are complicated yet serious issues among teachers at all educational levels. Though widely studied, research on them often focuses on pre-service or primary and middle school teachers, with little research on in-service university teachers. It is especially so in China. The present study thus examined anxiety, stress and their relations with demographic variables in in-service university teachers in China. 256 teachers from various universities in China answered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 25 publications
(60 reference statements)
7
18
0
1
Order By: Relevance
“…Although some respondents reported that anxiety could be a motivator and urged them to do better, more respondents reported it to be a debilitator, as found in studies on SL/FL learners' FLA (Horwitz et al, 1986;Liu & Xiangming, 2019;Tobias, 1979;Tum, 2014). As confided by the respondents, anxiety led to a series of bad consequences, the worst of which were bad sleep, depression, lowered devotion to teaching, lowered motivation to work, becoming nervous, bad-temper, inability to focus on something, gray hair, procrastination, sickness, and lowered confidence, as found in similar studies (Cheung & Hui, 2011;Liu & Yan, 2020;Robinson & Clay, 2005;Yazici & Altun, 2013). All these definitely affected the respondents' work and life.…”
Section: Effects Of Anxietysupporting
confidence: 61%
See 3 more Smart Citations
“…Although some respondents reported that anxiety could be a motivator and urged them to do better, more respondents reported it to be a debilitator, as found in studies on SL/FL learners' FLA (Horwitz et al, 1986;Liu & Xiangming, 2019;Tobias, 1979;Tum, 2014). As confided by the respondents, anxiety led to a series of bad consequences, the worst of which were bad sleep, depression, lowered devotion to teaching, lowered motivation to work, becoming nervous, bad-temper, inability to focus on something, gray hair, procrastination, sickness, and lowered confidence, as found in similar studies (Cheung & Hui, 2011;Liu & Yan, 2020;Robinson & Clay, 2005;Yazici & Altun, 2013). All these definitely affected the respondents' work and life.…”
Section: Effects Of Anxietysupporting
confidence: 61%
“…The present study revealed that major causes for teaching anxiety were concern about classroom teaching, research, other work and promotion, and interest and confidence in teaching. Similar to their counterparts in other contexts (Ahmed & Julius, 2015;Desouky & Allam, 2017;Liu & Yan, 2020;Parsons, 1973;Robinson & Clay, 2005;Yazici & Altun, 2013), the participants in the present study experienced (great) anxiety due to applying for projects and funds, writing up papers, getting papers published, and getting promoted. Meanwhile, they had to face heavy teaching load and worry about the effectiveness of their teaching and selfdevelopment.…”
Section: Sources Of Teaching Anxiety and Teacher Flasupporting
confidence: 57%
See 2 more Smart Citations
“…If the faculty stress would not be managed, this might be detrimental to the institution since it affects performance in the workplace. It is a challenge to ensure high-quality education when faculty in higher education can not cope with educational stress [31].…”
Section:  Issn: 2252-8806mentioning
confidence: 99%